Proceedings of the 28th International Conference on Software Engineering 2006
DOI: 10.1145/1134285.1134317
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian approach to diagram matching with application to architectural models

Abstract: IT system architectures, as well as other systems, are often described by formal models or informal diagrams. In practice, there are often a number of versions of a model, e.g. for different views of a system, divergent variants, or a series of revisions. Understanding how versions of a model correspond or differ is crucial, yet little work has been done on automated assistance for matching models and diagrams.We have designed a framework based on Bayesian methods for finding these correspondences automaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Tools differ in their underlying program representation, matching granularity, matching multiplicity, and matching heuristics. In prior work [23], we compared existing matching techniques [3,5,17,18,19,20,24,26,28,32,35,37] along these dimensions. Our survey found that fine-grained matching techniques often depend on effective mappings at a higher level.…”
Section: Background Program Element Matching Techniquesmentioning
confidence: 99%
“…Tools differ in their underlying program representation, matching granularity, matching multiplicity, and matching heuristics. In prior work [23], we compared existing matching techniques [3,5,17,18,19,20,24,26,28,32,35,37] along these dimensions. Our survey found that fine-grained matching techniques often depend on effective mappings at a higher level.…”
Section: Background Program Element Matching Techniquesmentioning
confidence: 99%
“…Many existing approaches to model merging concentrate on syntactic and structural aspects of models to identify their relationships and to combine them. For example, (Melnik, 2004) studies matching and merging of conceptual database schemata, (Mehra et al, 2005) proposes a general framework for merging visual design diagrams, describes an algebraic approach for merging requirements views, and (Mandelin et al, 2006) provides a technique for matching architecture diagrams using machine learning. These approaches treat models as graphical artifacts while largely ignoring their semantics.…”
Section: Behavioural Fusionmentioning
confidence: 99%
“…There are several approaches to this, including linear and nonlinear averages, and machine learning. Learning-based techniques have been shown to be effective when proper training data is available (Mandelin et al, 2006). At this stage, we do not have sufficient training data to employ such techniques.…”
Section: Combining Different Similarity Measuresmentioning
confidence: 99%
See 2 more Smart Citations